2021
DOI: 10.1002/cplu.202100072
|View full text |Cite
|
Sign up to set email alerts
|

Flat, Cα,β‐Didehydroalanine Foldamers with Ferrocene Pendants: Assessing the Role of α‐Peptide Dipolar Moments

Abstract: The foldamer field is continuously expanding as it allows to produce molecules endowed with 3D-structures and functions never observed in nature. We synthesized flat foldamers based on the natural, but non-coded, C α,β -didehydroalanine α-amino acid, and covalently linked to them two ferrocene (Fc) moieties, as redox probes. These conjugates retain the flat and extended conformation of the 2.0 5 -helix, both in solution and in the crystal state (X-ray diffraction). Cyclic voltammetry measure-ments agree with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 91 publications
3
23
0
Order By: Relevance
“…This condition is dramatically diverging from that observed in α‐ or‐3 10 ‐helical peptides, where the amide C=O groups align along the helix axis and generate important macro‐dipoles. In our recent contribution [8c] we have shown that the 2.0 5 ‐helix has indeed a negligible dipole moment, thus confirming the relevance of this feature in promoting electron/charge transfer in helical peptides. In that contribution we appended two ferrocene (Fc) probes to the ends of flat peptides, as we previously did with 3 10 ‐helical peptides [11] .…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…This condition is dramatically diverging from that observed in α‐ or‐3 10 ‐helical peptides, where the amide C=O groups align along the helix axis and generate important macro‐dipoles. In our recent contribution [8c] we have shown that the 2.0 5 ‐helix has indeed a negligible dipole moment, thus confirming the relevance of this feature in promoting electron/charge transfer in helical peptides. In that contribution we appended two ferrocene (Fc) probes to the ends of flat peptides, as we previously did with 3 10 ‐helical peptides [11] .…”
Section: Introductionsupporting
confidence: 64%
“…In the amide A region (Figure 2A and 2 C) the band at about 3440 cm −1 is due to the stretching of C‐terminal amide N−H, not involved in H‐bonds. The intense band at about 3385 cm −1 , that encompasses all other amide NH, has the typical frequency of the intra ‐residue (C 5 conformation) H‐bond observed in ΔAla peptides [8a,c,13] . In addition, in all peptides this frequency is unchanged, because the intra‐residue H‐bonds in the 2.0 5 ‐helix do not interconnect with residues that precede or follow.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations